MOBILE MANIPULATOR ROBOT PADA KASUS PEMINDAH BARANG - Irianti, Faradila; Firman, Ely; Muhammad iqbal nugraha; Yudhi (Politeknik Manufaktur Negeri Bangka Belitung, 2022)
The industrial world really expects an increase in performance by utilizing and creating the latest technology. Robot arm is one type of robot that is often used to perform various tasks to replace humans in the industrial world. By collaborating the function of the arm and wheel, it will produce the ability to move goods more effectively and efficiently. With a line tracing system or line detection, the mobile manipulator robot will move along the existing line to get to the place where the object is picked up, then the robot arm will function to pick up and put the object back to its destination. The output of this research is a mobile manipulator robot which has a maximum range of 237mm on the X-axis, 237mm on the Y-axis, and 224mm on the Z-axis and success in getting to the workpiece location using a line follower system while the manipulator with 3 DOF can reach the servo angle. a maximum of 120 degrees on the waist, 180 degrees on the upper and lower arms, and can clamp the workpiece with a rotating angle of up to 360 degrees.